Linear programming models in business - Smith, Derrick (Stockport : Polytech Publishers, 1973)
The book is aimed at intending O.R. practitioners. Much of the book is taken up with a full description of the way in which an LP model of a business situation can be built up. The basic assumptions, benefits, and underlying difficulties of models with the LP structure are described
Includes index.
Bibliography: p. 215.
rpm 23/01/2019
Loans
Keywords: Business